2021
DOI: 10.1021/acsnano.0c10526
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processed Organic/Silicon Nanowires Hybrid Heterojunction Solar Cells Using Organosilane Incorporated Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate) as Hole Transport Layers

Abstract: Hybrid heterojunction solar cells (HHSCs) using crystalline Si nanowires (SiNWs) as the absorber and conducting polymer poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) as the hole-selective transport layer (HTL) show great potential in both low-cost and high-power conversion efficiency (PCE). However, due to the poor wettability of the PEDOT:PSS solution on SiNWs, conformal coverage of PEDOT:PSS on SiNWs is not easy to achieve. Here, an effective method was developed to decrease the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Silicon (Si)-based Schottky junction/heterojunction solar cells having exhibited the potential to deliver a competitive power conversion efficiency (PCE) to the traditional pn junction counterparts, but with a simpler fabrication process, e . g ., low-temperature solution processing, have aroused increasing interest in recent years. , To date, various materials including PEDOT:PSS, carbon nanotubes (CNTs), graphene, and some metal oxides have been examined to make the Schottky junction/heterojunction with Si wafers. For these devices, the electron/hole transport layers (E/HTLs) that extract and transfer free electrons/holes and meanwhile block the holes/electrons from Si play an indispensable role. Developing effective and long-term stable E/HTL materials and the device fabrication processes suitable for Si-based Schottky junction/heterojunction solar cells has been a significant effort. …”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si)-based Schottky junction/heterojunction solar cells having exhibited the potential to deliver a competitive power conversion efficiency (PCE) to the traditional pn junction counterparts, but with a simpler fabrication process, e . g ., low-temperature solution processing, have aroused increasing interest in recent years. , To date, various materials including PEDOT:PSS, carbon nanotubes (CNTs), graphene, and some metal oxides have been examined to make the Schottky junction/heterojunction with Si wafers. For these devices, the electron/hole transport layers (E/HTLs) that extract and transfer free electrons/holes and meanwhile block the holes/electrons from Si play an indispensable role. Developing effective and long-term stable E/HTL materials and the device fabrication processes suitable for Si-based Schottky junction/heterojunction solar cells has been a significant effort. …”
Section: Introductionmentioning
confidence: 99%
“…For the PEDOT:PSS/Si HHSCs with the structure of "Front PEDOT:PSS," in which the PEDOT:PSS layer acts as the optical window, efficiencies of 13%-17% [13][14][15][16][17] were achieved with spin coated PEDOT:PSS HTL and vacuum deposited electron transport layer (ETL). Very recently, efficiencies above 18% 18,19 were reported on HHSCs in which both HTL and ETL were fabricated using solution technology, which makes spraying or printing high efficiency c-Si heterojunction solar cells possible in the future. Meanwhile, devices with the "Back PEDOT:PSS" structure, where doped Si layer served as the front side ETL and PEDOT:PSS HTL was spin coated at backside of the Si substrates to prevent the parasitic absorption of PEDOT:PSS, have also been investigated and the efficiencies have recently come up to 18.8% 20 on n-Si substrates and 20.6% 21 on p-Si substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The PEDOT:PSS/n‐type c‐Si heterojunction contact with an inversion layer contributes to the excellent charge separation and transport characteristics and demonstrating the potential for high power conversion efficiency (PCE). Thereby, PEDOT:PSS/Si hybrid heterojunction solar cells (HHSCs) in which n type c‐Si wafer serves as absorber and PEDOT:PSS functions as HTL have drawn significant attention due to promising PCE as well as simple and low temperature solution processing 6–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, many researchers have experimentally and theoretically investigated the field enhancement of submicron-structured Si materials for various shapes, including spheres, , dimers, disks, doughnuts, pillars, and coral structures . Research has demonstrated a large field enhancement in the visible to near IR regions, whereby the performances of solar cells, biomedical sensors, optical tweezers, and high-color light sources are improved in a wide spectral region.…”
mentioning
confidence: 99%